Chemical Workers Union Consortium Trains Trainers in Disaster Response While Building Both Resiliency in Disasters and Preparedness - Allen, Shari Glines; Morawetz, John S.; Ruttenberg, Ruth (Archives of Business Research, 2024)
This paper studies disaster training work of one of the original grantees of the Worker Training Program of the National Institute of Environmental Health Sciences: The International Chemical Workers Union Council (ICWUC) and its consortium of unions and national organizations. The consortium developed disaster train-the-trainer curriculum in English and in Spanish, so worker trainers would be poised to do training during, after, and in prevention of disasters. This paper reviews the program and its impact on affected communities – with both a historical perspective and with interviews of 20 of those who were trained to be disaster response trainers. At least half the trainees actively trained at one or more disaster sites provided important information to keep community residents safer and to help them build resilience in their communities. Other trainers have used their knowledge to improve their workplaces during a disaster or to help prevent mold contamination and other post-disaster hazards in underserved neighborhoods.